The Role of the Neutrophil-to-Lymphocyte Ratio in the Development of Heart Failure in Patients with Concomitant Hypertension, Type 2 Diabetes, and Obesity - Shelest, Borys; Babycheva, Oleksandra; Sadovenko, Olga; Kalmykov, Oleksii; Rodionova, Iulia; Sukhonos, Nataliia; Kovalova, Yuliia; Shelest, Oleksiy (Medicinski časopis, 2025)
Objective. Arterial hypertension, type 2 diabetes mellitus (T2DM), and obesity increase cardiovascular risk, including heart failure (HF). The neutrophil-to-lymphocyte ratio (NLR), a systemic inflammation marker, has been linked to adverse cardiovascular outcomes, but its role in HF development remains unclear. This study evaluated NLR as a predictor of HF in these patients.Methods. A total of 293 patients with essential hypertension, T2DM, and obesity were enrolled in a prospective study. They were categorized into two groups: HF group (n=85) and non-HF group (n=208). NLR was calculated from complete blood count results. HF was diagnosed based on the 2023 ESC guidelines and confirmed via biomarkers (NT-proBNP) or echocardiography. Patients were followed for 24 months.Results. Patients who developed HF had significantly higher NLR (3.39 ± 1.23 vs. 2.66 ± 1.14, p
Keywords: Neutrophil-Lymphocyte Ratio, Heart Failure, Hypertension, Diabetes Mellitus, Type 2, Obesity.